2008
DOI: 10.1073/pnas.0800156105
|View full text |Cite
|
Sign up to set email alerts
|

Sustained delivery of siRNAs targeting viral infection by cell-degradable multilayered polyelectrolyte films

Abstract: RNAi ͉ therapy ͉ hepatitis C virus ͉ hepatocyte ͉ liver

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 26 publications
1
59
0
Order By: Relevance
“…[218,219] Recently, Dimitrova et al [219] demonstrated, using hepatitis C virus infection (HCV) as a model, that siRNAs targeting the viral genome were efficiently delivered by PEM films. This delivery method resulted in a marked, dosedependent, specific, and sustained inhibition of HCV replication and infection in hepatocyte-derived cells.…”
Section: Localized Gene Therapy Of Dna and Rnamentioning
confidence: 99%
“…[218,219] Recently, Dimitrova et al [219] demonstrated, using hepatitis C virus infection (HCV) as a model, that siRNAs targeting the viral genome were efficiently delivered by PEM films. This delivery method resulted in a marked, dosedependent, specific, and sustained inhibition of HCV replication and infection in hepatocyte-derived cells.…”
Section: Localized Gene Therapy Of Dna and Rnamentioning
confidence: 99%
“…PEI25K/siRNA complexes were prepared as described previously with slight modification. 36 Briefly, 10 μg of siRNAs was dissolved in 150 μl of 150 mM NaCl and incubated for 10 min. Thirty-three microliters of PEI25K (5 mg/ml) in 150 mM NaCl was added to the siRNA solution, resulting in a nitrogen-to-phosphorus (N/P) ratio of 33.…”
Section: Methodsmentioning
confidence: 99%
“…Multilayered architectures have been shown to deliver drugs (26)(27)(28)(29) and DNA (30)(31)(32)(33)(34), but little is known about whether this technique is feasible for the sustained delivery of siRNAs. Dimitrova et al (2008) used multilayered polyelectrolyte films consisting of polylysine and polyglutamic acid as a precursor film and a hyaluronan-chitosan layer for the adsorption of PEI siRNA complexes that delivered siRNA to Huh7.5 cells (35). Interestingly, Neumann et al (2006) used a gelatin layer with Lipofectamine™ 2000 and siRNAs for high-throughput RNAi screening on microarray for mainly HeLa cells (36).…”
Section: Introductionmentioning
confidence: 99%